Depiction of women as the primary architects of their own oppression: a masculinist critique of El Saadawi’s Woman at Point Zero - Idris, Abdulrahman Abdulwaheed; Talif, Rosli; Ali Termizi, Arbaayah; Jujar Singh, Hardev Kaur (Australian International Academic Centre, 2018)
This paper focuses on the presentation of women oppression and emancipation in Nawal El Saadawi’s novel, Woman at Point Zero. The novel is specifically a call and an appeal to the women in her Egyptian society and the world at large on the need to revisit their activities and contribution toward the oppression, suppression, molestation, and brutality of their fellow women. Nawal El Saadawi presents with unique clarity, the unpleasant experience women are subjected to in her male-dominated society (Egypt). The novel aesthetically captures the oppression, sexual harassment, domestic aggression, and intimidation that the Egyptian women are subjected to in her patriarchal social milieu. Through a Masculinist study of the text, this paper not only submits that women create sa conducive atmosphere for the unhappiness of their own kinds but also subverts the author’s proposition of the way forward for the Egyptian women who are disenchanted under the atmosphere that is besieged with unfair treatment of the women. This essay unambiguously argues that El Saadawi’s understanding of women emancipation from the persistent violence on the women is outrageously momentary and unsatisfactory. Indeed, the novel has succeeded in subverting the stereotypical representation of the women as weak, passive, and physically helpless yet, the cherished long-lasting emancipation expected from her oppressed women could not be fully achieved. The novelist portrays a resilient and revolutionary heroine whose understanding of women liberation leaves every reader disconcerted. The paper examines the oppression that the heroine, Firdaus suffers from men and her fellow women and how she eventually achieved a momentary emancipation.